Evaluation of the antioxidant, anti-inflammatory, and anti-tumoral properties of bioactive compounds extracted from murta berries (Ugni molinae T.) dried by different methods - López, Jéssica; Vega-Gálvez, Antonio; Ah-Hen, Kong S.; Rodríguez, Angela; Quispe-Fuentes, Issis; Delporte, Carla; Valenzuela-Barra, Gabriela; Arancibia, Yennyfer; Zambrano, Angara (Frontiers in Plant Science, 2023)
This study evaluated the effects of different drying methods (freeze-, vacuum-, infrared-, convective-, and sun-drying) on biological properties in berries from the Chilean murta (Ugni molinae Turcz) shrub. The chemical properties of dried berries differed significantly based on the drying method: freeze-dried murta berries showed increased total phenolic content extracted over fresh samples and dried. In addition, this lyophilized stood out in its antioxidant potential, in both assays evaluated (DPPH and ORAC), compared to the other drying methods. Notwithstanding, vacuum and infrared murta dried also showed a higher ORAC value. Antioxidant potential was significantly associated with phenolic compounds, catechin, and pyrogallol were the most abundant phenolic compounds and present in all samples. The anti-inflammatory activity was most effective under freeze-drying and vacuum-drying conditions. Moreover, vacuum-drying and infrared drying best preserved the anti-tumoral effect on cancer cells.